2007
DOI: 10.1080/10428190701422059
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value and diagnostic accuracy of F-18-fluoro-deoxy-glucose positron emission tomography treated grade 1 and 2 follicular lymphoma

Abstract: F-18-fluoro-deoxy-glucose positron emission tomography (PET) is a powerful tool for the imaging of aggressive B-cell lymphomas. In contrast, there is relatively little data on PET in follicular lymphoma grade 1 (FL-1) and grade 2 (FL-2). In this manuscript, we present our findings utilizing PET in treated FL-1 and FL-2. A retrospective review of patients who underwent PET examinations at our institution produced 95 PET examinations among 31 patients with FL-1 and FL-2. PET was obtained at initial staging, mid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 32 publications
3
36
0
2
Order By: Relevance
“…Published literature includes 10 retrospective analyses [9][10][11][12][13][14][15][16][17][18] and 1 prospective one [19]: pooled analysis of 356 patients revealed that 24% were upstaged from Stage I-II to Stage III-IV. Baseline PET also showed to have a high prognostic value, irrespective of FLIPI [10,11,17,19].…”
Section: Issue 1: Staging (Consensus-based Recommendations)mentioning
confidence: 99%
“…Published literature includes 10 retrospective analyses [9][10][11][12][13][14][15][16][17][18] and 1 prospective one [19]: pooled analysis of 356 patients revealed that 24% were upstaged from Stage I-II to Stage III-IV. Baseline PET also showed to have a high prognostic value, irrespective of FLIPI [10,11,17,19].…”
Section: Issue 1: Staging (Consensus-based Recommendations)mentioning
confidence: 99%
“…With regard to the type of PET scanner, five studies used combined PET/CT (15,(17)(18)(19)(20), one studies used standalone PET (21), and two studies used both (14,16). The criteria of treatment response assessment of PET results somewhat varied across the studies, as summarized in Table 1.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…The majority of included patients underwent CIT such as R-CHOP or R-CVP according to the policy of institutions or oncologists, whereas participants in one study underwent RIT (18). In terms of reference standard, all included studies reported that they used all available clinical information including imaging follow-up as proof of disease recurrence/progression, whereas only two studies specifically mentioned histologic assessment for evaluation of recurrence/progression (14,19).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 2 more Smart Citations